Kepemimpinan dalam Islam - Moh Amin (Resolusi: Jurnal Sosial Politik, 2019)
Leadership is the main thing in human life. This article describes some leadership models in general. By referring to some literature, this article also tries to explore the leadership in Islam. Some of the bases can be seen in the Qur'an and Hadist prophet. With the library review study model, this article concludes on the importance of fair leadership as the basis of Islam.